The Application and Prospects of Intellectual Property-Based Credit Guarantees in Banking Practices in Serang City - Sulasno Sulasno; Ardita Octavia; Inge Dwisvimiar; Juhary Ali (Universitas Lampung, 2026)
The use of intellectual property (IP) as collateral for bank loans, although regulated under Government Regulation No. 24/2022, still faced significant challenges in practice. These included difficulties in determining fair market value due to IP’s intangible nature, the lack of standardized valuation systems, complex execution mechanisms in cases of default, and the limited readiness of specialized appraisal institutions. Banks applied prudential principles because IP was considered a higher-risk asset. This study used a qualitative empirical juridical approach based on primary, secondary, and tertiary data analyzed descriptively. The results showed that IP certificates had strong legal and economic prospects as collateral for creative entrepreneurs and rights holders, as they already met legal criteria. However, their practical use as bank collateral in Serang City remained limited and not yet optimal.